2012
DOI: 10.1007/s00586-012-2235-x
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive electrospun scaffold for annulus fibrosus repair and regeneration

Abstract: Purpose Annulus fibrosus (AF) tissue engineering is gathering increasing interest for the development of strategies to reduce recurrent disc herniation (DH) rate and to increase the effectiveness of intervertebral disc regeneration strategies. This study evaluates the use of a bioactive microfibrous poly(L-lactide) scaffold releasing Transforming Growth Factor (TGF)-b1 (PLLA/TGF) for the repair and regeneration of damaged AF. Methods The scaffold was synthesized by electrospinning, with a direct incorporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 27 publications
1
54
0
Order By: Relevance
“…Indeed, tissue regeneration has made rapid progresses in recent years, making possible the synthesis of constructs that closely mimic the structure and properties of native tissues. Many new promising biomaterials have been recently described [23][24][25] and need to be tested in valuable animal models. Various agencies, such as Medicines and Healthcare products Regulatory Agency (MHRA), National Institute for Health and Clinical Excellence (NICE), Central Office for Research Ethics Committees (COREC) and US Food and Drug Administration (FDA), will require evidences of successful animal works, to sanitize any permissions given to proceed to human work [3].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, tissue regeneration has made rapid progresses in recent years, making possible the synthesis of constructs that closely mimic the structure and properties of native tissues. Many new promising biomaterials have been recently described [23][24][25] and need to be tested in valuable animal models. Various agencies, such as Medicines and Healthcare products Regulatory Agency (MHRA), National Institute for Health and Clinical Excellence (NICE), Central Office for Research Ethics Committees (COREC) and US Food and Drug Administration (FDA), will require evidences of successful animal works, to sanitize any permissions given to proceed to human work [3].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the use of different bioactive peptides as substitutes for cell therapy has been successfully tested in cardiac regeneration and other specialties. 17,[39][40][41][42] In the present study, we selected RGD, a tripeptide composed of arginine-glycine-aspartate that mimics the integrin-binding site of cells and the extracellular matrix 43 and has already been successfully tested as a biofunctionalization motif. 44 Grafting of RGD on a polymer was compared, again in a head-to-head fashion, with ADSC selected because of their ease of procurement, richness of their secretome, and potential for human applications.…”
Section: Figmentioning
confidence: 99%
“…Lazebnik et al, (2011) used a biomimetic strategy by combining porcine chondrocyte cell seeded agarose gel surrounded by cell seeded electrospun polycaprolactine ibres and observed that cells were viable, well distributed and orientated themselves in the direction of the ibres [128]. Successful incorporation of growth factors to enhance regeneration has also been shown in electrospun scafolds [129]. Furthermore, biphasic scafolds consisting of a hydrogel NP centre surrounded by a polymeric electrospun AF (2014) conducted an in vivo eicacy study whereby bone marrow derived MSCS were encapsulated within hydrogels, incorporated with anti-angiogenic factors and implanted into ovine disc; following 12 weeks no signiicant diference in biomechanical properties was observed between implanted and untreated discs and disc height and degeneration score deteriorated for all implant treated discs [131].…”
Section: Cellular Biomaterials For Disc Degenerationmentioning
confidence: 99%